Modelling the production of NOx in coal burning - Èarnogurská Mária (Acta Montanistica Slovaca, 2000)
The paper describes a mathematical model of NOx production derived with the help of dimensional analysis. The model results are compared with direct measurements of the real work. Model laws are presented as well, which enable to transfer the results of the mathematical model to any other work fulfilling the condition of geometric and mechanical similarity.